2006
DOI: 10.1007/s00595-006-3293-7
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer Detected by Mass Screening Over a Period of 16 Years at a Health Care Center in Japan

Abstract: Manipulation is adequate as an initial screening method for thyroid examination, and ultrasonography may not always be required. Moreover, it is necessary to consider gender when referring a patient to a specialist and when deciding on the indications for surgery to remove a thyroid tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…A smaller proportion of these tumors is detected during imaging of the neck for other purposes, such as parathyroid evaluation, using (for example) carotid Doppler, CT, and FDG-PET. In Korea and Japan, however, many health care centers perform ultrasonography during initial examination of the thyroid [ 5 - 7 ], and impalpable nodules have increasingly been discovered. Korea is a country without iodine deficiency [ 17 ] and many thyroids have only one nodule, making ultrasound an excellent method to detect PTMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A smaller proportion of these tumors is detected during imaging of the neck for other purposes, such as parathyroid evaluation, using (for example) carotid Doppler, CT, and FDG-PET. In Korea and Japan, however, many health care centers perform ultrasonography during initial examination of the thyroid [ 5 - 7 ], and impalpable nodules have increasingly been discovered. Korea is a country without iodine deficiency [ 17 ] and many thyroids have only one nodule, making ultrasound an excellent method to detect PTMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Most PTMCs are incidentally detected by histological analysis of thyroid glands removed for preoperatively diagnosed benign diseases, or are indirectly diagnosed because of the presence of enlarged metastatic cervical lymph nodes or distant metastases [ 3 , 4 ]. In Korea and Japan, however, where ultrasonography is frequently used in the initial examination of thyroid glands [ 5 - 7 ], the incidence of PTMC has increased explosively [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It includes cases with equivocal features of PTC (Fig. 3), features suggestive of chronic thyroiditis and malig- ciently select patients with thyroid nodules for surgery because the risk of malignancy of follicular neoplasm was within the range of baseline risk of malignancy, which was estimated to be about 10-20% in Western countries and 12.4-15.9% in Japan [6,7,[37][38][39][40]. Among a series of 1044 surgically treated patients at Kuma Hospital, Kobe, Japan, in 2000, Mori et al reported that the risk of FTC was 7.9% (22/279) in cases with nodular thyroid diseases (other types of malignancy were excluded) and incidental PTC was found in 7.2% (20/277) of patients with benign nodular disease, with the total risk of malignancy (risk of FTC in index nodule and risk of incidental PTC) in patients with a thyroid nodule (other types of malignancy were excluded) being 14.0% (42/299) [39].…”
Section: International Reporting Systems Of Thyroid Fna Cytology and mentioning
confidence: 99%
“…ROIs were drawn to include as much of the lesions, whilst avoiding cysts and overt calcifications. e following quantitative parameters were measured: [1] iodine concentration (mg/mL) at 120 kVp and [2] CT attenuation curve slope, plotted from 40 keV to 190 keV ( Figure 1).…”
Section: Measurement Of Iodinementioning
confidence: 99%
“…yroid nodules are found with increasing frequency, likely due to the widespread use of imaging modalities including ultrasonography (US) and computed tomography (CT). Although more than 95% of the detected nodules are clinically insignificant benign lesions, thyroid nodules are clinically important as they may represent thyroid malignant tumor [1,2]. Despite an increase in the prevalence of malignant thyroid nodules and invasive examinations, the mortality rate has remained unchanged from 1973; this observation is attributed to overdiagnosis of subclinical thyroid nodules [3,4].…”
Section: Introductionmentioning
confidence: 99%